Modification of Carbon Nanotubes via Birch Reaction for Enhanced HER Catalyst by Constructing Pearl Necklace‐Like NiCo 2 P 2 –CNT Composite - Gao, Saisai; Zhang, Yin; Zhang, Yanjun; Wang, Bin; Yang, Shengchun (Small (Weinheim an der Bergstrasse, Germany), 2018)
Combining transition metal phosphides (TMPs) with carbon nanotubes (CNTs) is a promising and proven approach to enhance their performance in the electrochemical hydrogen evolution reaction (HER), due to the excellent conductivity and stability of CNTs. Generally, the deep oxidation of CNTs to form oxygen‐containing groups on their surface is indispensable before combining them with TMPs. However, such approaches inevitably introduce a large number of defects to CNTs and apparently decrease their stability and electrical conductivity. Hence, fabricating TMP–CNT composites which does not come at the expense of CNTs' high electrical conductivity is quite desirable. In this work, alkylated CNTs (named as ACNT) functionalized via the Birch reaction are used to prepare the pearl necklace‐like NiCo 2 P 2 –ACNT composites for electrocatalysts toward HER in acidic and alkaline conditions, respectively. The X‐ray photoelectron spectroscopy, transmission electron microscope, and Fourier transform infrared spectroscopy characterizations indicate that the ACNTs are well modified with functional groups and keep their structural integrity, thereby maximizing their excellent conductivity. Compared to bare NiCo 2 P 2 and the NiCo 2 P 2 –CNT composites prepared with mildly oxidized CNTs and deeply oxidized CNTs, the NiCo 2 P 2 –ACNTs show far better HER performance and much faster kinetics.